Analysis of Arsenic Species in Processed Rice Bran Products Using HPLC‐ICP‐MS. Issue 10 (13th September 2018) - Kim, So Young; Seo, Dongwon; Yoo, Miyoung; Lee, Kwang‐Geun
Abstract : Abstract: The purpose of this study was to compare the content of arsenic species (As(V), monomethylarsonic acid [MMA], As(III), and dimethylarsinic acid [DMA]) in products, such as bran powder and tablets, using high‐performance liquid chromatography‐inductively coupled plasma mass spectrometry, and to determine the risk of human exposure to inorganic arsenic (iAs). The products presented As(III) > As(V) > DMA > MMA, at 241.03 to 579.35, 43.41 to 271.91, 15.16 to 30.43, and limit of quantification to 14.31 μg/kg, respectively. The contents of arsenic species tended to differ among the products ( P  < 0.05). When the maximum level (0.2 mg/kg) of iAs in white rice was applied to products, it exceeded 1.4 to 3.3 times as 284.43 to 767.10 μg/kg. Also, if more than 109.42 g/day of rice bran powder product containing 767.10 μg/kg as iAs was ingested, the provisional tolerable weekly intake (9.0 μg/kg body weight/wk) was exceeded. Practical Application: This study could provide analysis necessary of As for defining an accurate risk assessment of products and tablets containing rice bran powder. In addition with this study, the regulations for As contents in rice bran power products would be set.